Empowering Female Climate Change Activists in the Global South The Path Toward Environmental Social Justice - Spitzer, Peggy Ann (2023)
strong The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online.strong The COP27 climate change conference in Sharm El Sheikh, Egypt made it clear that fighting global warming will require continuing commitment, cooperation, and collaborative action from multiple constituencies around the world. Urging readers from the Global North to rethink their approaches and potential contributions to long-term change, Empowering Female Climate Change Activists in the Global South explains how woman climate change leaders are confronting patriarchal structures to achieve social justice. Examining the lived experiences of woman climate change activists based in rural areas, Peg Spitzer presents eighty-five original interviews that feature women whose careers in business, education, politics, and the arts have championed women's rights in Asia, environmental defenders who have established projects in Asia, Africa, and Latin America, and woman farmers in three Indian villages who have faced climate-related droughts and floods. Suggesting ways in which successful climate change amelioration and adaptation led by women in the Global South may be replicated elsewhere, Spitzer also considers how NGOs and other organizations from the Global North can best contribute to facilitating positive changes in the communities where they work by focusing on empathetic cooperation. Addressing the urgent need to develop gender-just solutions that uplift and empower those who are experiencing environmental degradation in their communities, Empowering Female Climate Change Activists in the Global South uncovers the flaws in current combative structures and strategies and re-examines scholarly research at the nexus of feminism, transnational advocacy, and hierarchies of need.